The Effects of Text Messaging for Increasing the Rate of long-acting Reversible Contraception use in Teenage Pregnancy: A Randomized Controlled Trial - Kusuma Meesin; Nirun Intarat; Nidhikul Temeiam; Kunthida Kingsawad (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: A teenage pregnancy rate is a one of SDGs goal. Thailand had a teenage pregnancy rate higher inAsia-Pacific from less developed regions. A one of cause is a sex when they was young. This study is aimed tostudy an effective of a text messaging of teenage pregnant to the long-acting reversible contraception.Materials and Methods: This is a randomized controlled trial. The study was an effective of a text messaging ofteenage pregnant to the long-acting reversible contraception. A samples had 2 group from teenage pregnant in SiSaKet hospital. The control group was 212 samples. The trail group was 212 samples.Result: The control group had a standard care of postpartum. The trial group had a standard care of postpartumand a text message about long-acting reversible contraception. The researcher were following a both sample. Theyfound a trial group had a reversible contraception higher than a control group at a significant level. (P-value<0.001)Conclusion: Present, a communication is important onthe digital time especially in teenager. A one of measurementpostpartum teenager in this time is a text message. It will be reducing a repeat pregnant among teenage.